A study of traditional healer’s herbal recipes for asthma treatment - จิตจำ, ศรินทร์รัตน์; เลาหประภานนท์, สิริรัตน์; หะยียะห์ยา, วสันต์; ขนิษฐา, ณัฐ (Journal of Medicine and Health Sciences, 2019)
Abstract This research is a qualitative research by semi-structured interviews and participant observation. This research aimed to study traditional healer’s herbal recipes of asthma treatment. The subject are 4 traditional healers lived in southern, Thailand. The data were analyzed using descriptive, classified into categories and compare herbal with study sites. The result revealed 4 traditional healers were male, average 67 years old, had treated their patient average 36 years and inheriting knowledge from their ancestors. All traditional healers have similar asthma treatment knowledge, explained that asthma is a respiratory disease due to phlegm in the throat which affected to phlegm in the thorax. Resulting, the pharynx and thorax are phlegm blocked or sometimes constricted. There are several causes of asthma including genetic, over high or over low temperature, environment such as dust, smoke, pollen, unwholesome food and anxiety. The symptoms were coughs, phlegm, mucus in the bronchial area, dyspnea and sometime wheezing. All traditional healers advise patients by observed and avoided factors that cause symptoms. They treated with herbal recipe, collected in 9 recipes, the herbal that can be used 33 species such as Solanum aculeatissimum Jacq., Embelia ribes Burm.f., Citrus aurantiifolia (Christm.) Swingle, Musa paradisiaca L. Solanum trilobatum L., Zingiber montanum (J.Koenig) Link ex A.Dietr., Honey bee, Magnesium sulfate (MgSO 4), Menthol (C10H20O) etc. The most properties herbs were cough and expectorate. The most pharmacological effect was anti-inflammatory. There are 4 species which interested in asthma treatment herbs were Datura metel L., Schefflera leucantha R.Vig., Alpinia galanga (L.) Willd. and Acorus calamus L. because of the traditional Thai medicinal properties correspond with pharmacological effects in the asthma treatment.